Numerical study on the characteristics of the seismic response of subway shield tunnels beneath rock mountains: A case study in China. Issue 5 (October 2021) - Yao, Erlei; Sun, Qining; Li, Weichao; Yu, Miao; Liu, Meishan
Abstract: In this study, we investigated the characteristics of the seismic response of a subway shield tunnel beneath a rock mountain through the finite-element method based on a practical subway tunnel project in China. We discuss the influence of the spectral nonstationarity of seismic motion on tunnel responses. First, a set of quasistationary (QS) and fully nonstationary (FN) bedrock motions were artificially simulated. Second, the background information of the referenced project was briefly discussed, and correspondingly, several refined numerical models were established. Finally, the mutual relationship between a subway tunnel and the overlying rock mountains under QS bedrock motions was studied, and the results under the QS and FN bedrock motions were compared to clarify the effect of the spectral nonstationarity of ground motions. We found that i) an overlying rock mountain can suppress the acceleration response of an underground tunnel, and combined with the seismic motion, high confining pressure owing to the existence of an overlying mountain aggravates the radial shear-stress response and damage to the tunnel; ii) the spectral nonstationarity of input motions results in higher acceleration responses at the mountaintop and on the tunnel and causes greater radial shear stress and damage to the tunnel, even though the input PGAs and waveforms for QS and FN motions are the same. Therefore, artificial seismic motions exhibiting spectral nonstationarity may provide conservative results.